Tantalum oxide / carbon loaded high-stability platinum-based fuel cell cathode catalyst and preparation method thereof
Through the highly stable platinum-based fuel cell cathode catalyst supported by tantalum oxide/carbon, the dissolution and agglomeration of platinum nanoparticles caused by carbon support corrosion is solved, and efficient catalytic activity and stability is achieved, which is suitable for fuel cell applications.
Patent Information
- Application Number
- CN202411882056.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-05-02
AI Technical Summary
The corrosion of existing fuel cell cathode catalysts under acidic conditions leads to the dissolution and agglomeration of platinum nanoparticles, resulting in loss of catalyst performance, and poor conductivity of metal oxides limits their application.
A high-stability platinum-based fuel cell cathode catalyst supported by tantalum oxide/carbon is used to mix metal tantalum and carbon source by ultrasonic method, heat treatment is used to generate a tantalum oxide/carbon support, and platinum nanoparticles are uniformly loaded on its surface to improve the dispersion and utilization of platinum.
The catalyst showed high stability in the accelerated aging test. The average particle size of the platinum nanoparticles was 3.0 nm, which maintained high catalytic activity and stability. The peak power density reached 2.27W cm-2 and the performance retention rate was 90%.
Smart Images

Figure CN119920912A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of fuel cell cathode catalysts, and in particular relates to a tantalum oxide / carbon-loaded high-stability platinum-based fuel cell cathode catalyst, and a preparation method and application thereof. Background Art
[0002] Proton exchange membrane fuel cells (PEMFCs) can convert the chemical energy stored in hydrogen fuel into electrical energy. Their high efficiency and zero carbon emissions make them an ideal power source to replace internal combustion engines. However, their cathode oxygen reduction reaction (ORR) is slow and requires a large amount of platinum metal catalysts. However, the reserves of platinum-based metals in the earth's crust are scarce and expensive, which seriously affects the commercialization of PEMFC. Therefore, it is urgent to develop low-platinum catalysts that are both highly active and stable.
[0003] As an important component of the catalyst, the carrier not only affects the particle size, dispersion and specific surface area, but also affects the transfer of protons and electrons, further affecting the performance of the catalyst. Therefore, the activity and stability of platinum-based catalysts can be effectively improved by changing the carrier. For example, Liu et al. (Chong, L.; Wen, JG; Kubal, J.; Sen, FG; Zou, JX; Greeley, J.; Chan, M.; Barkholtz, H.; Ding, WJ; Liu, DJ, Ultralow-loading platinum-cobalt fuel cell catalysts derived from imidazolate frameworks. Science, 2018, 362, 1276-1281) proposed a nanocatalyst with Co-NC as the carrier and ultra-low platinum loading (2-3wt%), whose mass-normalized activity can reach 1.77AmgPt-1, and its durability reaches the international advanced level;
[0004] Chen Yaping's team (Chen, Y, P.; Zheng, X, SH.; Cai, J, Y.; Zhao, G, Q.; Zhang, B, X.; Luo, Zh, X.; Wang, G, M.; Pan, H, G.; Sun, W, P., Sulfur Doping Triggering Enhanced Pt-NCoordination in Graphitic Carbon Nitride-Supported Pt Electrocatalysts toward Efficient Oxygen Reduction Reaction. ACS Catalysis 2022, 12 (12), 7406-7414) prepared S-doped graphitic carbon nitride (SGCN)-supported platinum electrocatalysts and designed a highly active interface to achieve fast oxygen reduction reaction (ORR). S doping regulates the coordination and electronic structure of Pt, making the adjacent C and N atoms electron-deficient, thereby enhancing the metal-support interaction.
[0005] The activity and stability of platinum-based catalysts can be improved by regulating the support, but carbon materials are usually oxidized to CO and CO under acidic conditions. 2, and leads to the dissolution and ripening of platinum nanoparticles, resulting in loss of catalyst performance (Sui, S., Wang, X, Y., Zhou, X, T.; Su, Y, H.; Riffatc, S.; Liu, C, J., A comprehensive review of Ptelectrocatalysts for the oxygen reduction reaction: Nanostructure, activity, mechanism and carbon support in PEM fuel cells. J. Mater. Chem. A, 2017, 5, 1808). The strong antioxidant ability of metal oxides can effectively eliminate the problem of catalyst specific surface area loss caused by carbon support corrosion, thereby significantly improving the stability of the catalyst. For example, the Xing Wei team (Yang, L, T.; Hou, S.; Zhu, S, Y.; Shi, Z, P.; Wang, X.; Jiang, J, D.; Chu, Y, Y.; Bai, J, S.; Wang, Y.; Zhang, L, J.; Jiang, Z.; Liu, C, P.; Xing, W.; Ge, J, J., Stabilizing Pt Electrocatalysts via Introducing Reducible Oxide Support as Reservoir of Electrons and Oxygen Species. ACS Catalysis 2022, 12(21), 13523-13532) developed a highly stable and active Pt-Nb2O5 catalyst, introducing reducible Nb2O5 as a reservoir for electrons and oxygen species. Benefiting from the corrosion resistance and strong metal-support interaction of Nb2O5, the Pt-Nb2O5 catalyst shows negligible activity decay after 70 k cycles at potentials between 0.6 and 1.0 V and maintains good stability even at higher voltages.
[0006] However, due to the poor conductivity of metal oxides, their catalytic performance cannot be fully expressed, limiting their practical application in fuel cells. At the same time, there are fewer active sites on the surface of metal oxides, and platinum nanoparticles are prone to agglomeration to form larger nanoparticles, which reduces the atomic utilization of platinum. Therefore, it is still necessary to further modify the carrier to prepare a platinum-based fuel cell cathode catalyst with high stability, thereby effectively improving the activity and stability of the catalyst under low-platinum conditions in fuel cells. Summary of the invention
[0007] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0008] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0009] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a tantalum oxide / carbon-supported high-stability platinum-based fuel cell cathode catalyst.
[0010] In order to solve the above technical problems, the present invention provides the following technical solutions: comprising:
[0011] A metal tantalum source is dissolved in anhydrous ethanol and subjected to ultrasonic treatment to obtain a metal tantalum solution, a carbon source is added thereto, and after ultrasonic treatment, a black solid is obtained by rotary evaporation, wherein the mass ratio of the metal tantalum source to the carbon source is 1:1 to 1:10;
[0012] The black solid is heat-treated in a reducing atmosphere, and then naturally cooled to room temperature to obtain a tantalum oxide / carbon carrier;
[0013] Tantalum oxide / carbon carrier is dispersed in ethylene glycol, stirred in chloroplatinic acid aqueous solution added after ultrasound, condensed and refluxed in an oil bath after adjusting the pH of the solution, naturally cooled to room temperature after treatment, filtered and dried to obtain a tantalum oxide / carbon-supported high-stability platinum-based fuel cell cathode catalyst, wherein the platinum loading is 10wt.% to 50wt.%.
[0014] As a preferred embodiment of the method for preparing the tantalum oxide / carbon-supported high-stability platinum-based fuel cell cathode catalyst of the present invention, the metal tantalum source includes one or more of tantalum chloride and tantalum nitrate.
[0015] As a preferred embodiment of the method for preparing the tantalum oxide / carbon-supported high-stability platinum-based fuel cell cathode catalyst of the present invention, the carbon source is conductive carbon black.
[0016] As a preferred embodiment of the method for preparing the tantalum oxide / carbon-loaded high-stability platinum-based fuel cell cathode catalyst of the present invention, the ultrasonic time of dissolving the metal tantalum source in anhydrous ethanol is 0.5 to 2 hours, and the ultrasonic time after adding the carbon source thereto is 3 to 6 hours.
[0017] As a preferred embodiment of the method for preparing the tantalum oxide / carbon-supported high-stability platinum-based fuel cell cathode catalyst of the present invention, the reducing atmosphere is a mixture of hydrogen and argon, wherein the volume ratio of hydrogen to argon is 17-19:1-3.
[0018] As a preferred embodiment of the method for preparing the tantalum oxide / carbon-supported high-stability platinum-based fuel cell cathode catalyst of the present invention, the heating rate of the heat treatment is 1-10°C min -1 The heat treatment temperature is 500-1000° C., and the heat treatment time is 0.5-3 h.
[0019] As a preferred embodiment of the method for preparing the tantalum oxide / carbon-supported high-stability platinum-based fuel cell cathode catalyst of the present invention, the pH of the chloroplatinic acid aqueous solution is adjusted to 9-12.
[0020] Another object of the present invention is to provide a tantalum oxide / carbon-supported platinum-based fuel cell cathode catalyst with high stability.
[0021] To solve the above technical problems, the present invention provides the following technical solution: the platinum nanoparticles in the high-stability platinum-based fuel cell cathode catalyst are uniformly loaded on the surface of the tantalum oxide / carbon carrier, and the average particle size of the platinum nanoparticles is 3.0 nm.
[0022] The high-stability platinum-based fuel cell cathode catalyst has no obvious performance degradation after undergoing 90,000 cycles of accelerated aging test in a 0.1 mol / L perchloric acid solution;
[0023] Peak power density in MEA reaches 2.27 W cm -2 After 50,000 cycles of accelerated aging test, the performance retention rate is 90%
[0024] Beneficial effects of the present invention:
[0025] Aiming at the stability problems of the cathode catalyst of proton exchange membrane fuel cell (PEMFC) in the prior art, such as the dissolution of platinum due to the corrosion of carbon carrier, the loss of specific surface area caused by particle agglomeration, and the decline of catalytic activity, the tantalum oxide (TaOx) composite carrier loaded with platinum catalyst provided by the present invention utilizes the limiting effect of carbon surface mesopores to limit the excessive growth of metal oxides, and generates low-oxidation state amorphous TaO at high temperature. x , make TaO x Evenly dispersed in the carbon matrix in the form of small particles. Pt is selectively deposited on TaO xIn terms of the structure, the dispersion of platinum nanoparticles is improved, platinum is used to the maximum extent, the utilization rate of precious metals is increased, and the dissolution, agglomeration and Ostwald ripening of platinum particles are greatly reduced. At the same time, the carbon in the carrier solves the problem of poor conductivity of metal oxides, so that their performance is expressed in MEA. The prepared TaO x Compared with existing commercial catalysts, the loaded high-stability platinum-based fuel cell cathode catalyst has higher catalytic activity and better stability, effectively solving the above-mentioned technical problems. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0027] Figure 1 The X-ray diffraction pattern of the tantalum oxide / carbon support prepared in Example 1 of the present invention;
[0028] Figure 2 This is a transmission electron microscope image of a tantalum oxide / carbon-supported high-stability platinum-based fuel cell cathode catalyst prepared in Example 1 of the present invention;
[0029] Figure 3 The particle size distribution result of the dilute tantalum oxide / carbon-supported high-stability platinum-based fuel cell cathode catalyst prepared in Example 1 of the present invention;
[0030] Figure 4 The stability test results of the tantalum oxide / carbon-supported high-stability platinum-based fuel cell cathode catalyst prepared in Example 1 of the present invention in a three-electrode system;
[0031] Figure 5 The stability test results of the tantalum oxide / carbon-supported high-stability platinum-based fuel cell cathode catalyst in MEA prepared in Example 1 of the present invention.
[0032] Figure 6 The stability test results of the tantalum oxide / carbon-supported high-stability platinum-based fuel cell cathode catalyst prepared in Comparative Example 1 of the present invention in a three-electrode system;
[0033] Figure 7 The stability test results of the tantalum oxide / carbon-supported high-stability platinum-based fuel cell cathode catalyst prepared in Comparative Example 2 of the present invention in a three-electrode system;
[0034] Figure 8The stability test results of the tantalum oxide / carbon-supported high-stability platinum-based fuel cell cathode catalyst prepared in Comparative Example 3 of the present invention in a three-electrode system.
[0035] Fig. 9 The stability test results of the tantalum oxide / carbon-supported high-stability platinum-based fuel cell cathode catalyst prepared in Comparative Example 3 of the present invention in a three-electrode system. DETAILED DESCRIPTION
[0036] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0037] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0038] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0039] Unless otherwise specified, the raw materials used in the present invention are all commercially available chemical analysis grade in the art.
[0040] Example 1
[0041] This embodiment provides a method for preparing a tantalum oxide / carbon-supported high-stability platinum-based fuel cell cathode catalyst, specifically:
[0042] 1) Weigh 100 mg of tantalum chloride into a 100 ml beaker, add 30 ml of anhydrous ethanol, and ultrasonicate for 1 h to obtain a tantalum chloride solution, add 200 mg of conductive carbon black (EC-300J) thereto, the mass ratio of the metal tantalum source to the carbon source is 1:2, and ultrasonicate for 2 h before rotary evaporation to obtain a black solid;
[0043] 2) The black solid was placed in a tube furnace and heat treated in a 5 vol% argon-hydrogen mixed gas at a heating rate of 5 °C min -1 , heat treatment temperature is 650°C, time is 2h, and then naturally cooled to room temperature to obtain tantalum oxide / carbon carrier;
[0044] 3) 40 mg of tantalum oxide / carbon support was dispersed in 50 mL of ethylene glycol, ultrasonicated for 2 h, 1.40 mL of chloroplatinic acid solution (7.4 mg Pt / mL) was added, stirred for 0.5 h, and then the solution pH was adjusted to 10.7 with 1 M sodium hydroxide, condensed and refluxed in an oil bath at 130 ° C for 3 h, and filtered after natural cooling to room temperature. After drying, a tantalum oxide / carbon-supported high-stability platinum-based fuel cell cathode catalyst with a platinum loading of 20 wt% was obtained.
[0045] Figure 1 This is an X-ray diffraction characterization diagram of the tantalum oxide / carbon-supported high-stability platinum-based fuel cell cathode catalyst of this embodiment. It can be seen that the platinum nanoparticles in the obtained catalyst have good crystallinity.
[0046] Figure 2 This is a transmission electron microscope characterization image of the tantalum oxide / carbon-supported high-stability platinum-based fuel cell cathode catalyst of this example. It can be seen that the platinum nanoparticles in the obtained catalyst are uniformly supported on the surface of the carrier.
[0047] The particle size statistics of the high stability platinum-based fuel cell cathode catalyst supported by tantalum oxide / carbon were analyzed. Figure 3 As shown, it can be seen that the average particle size of the nanoparticles is 3.0 nm, the particle size is small and the distribution is uniform, which is conducive to exposing more catalytic active sites.
[0048] The accelerated aging test of the high-stability platinum-based fuel cell cathode catalyst supported by tantalum oxide / carbon was carried out in 0.1 mol / L perchloric acid solution. The results are as follows Figure 4 As shown, the catalyst showed no obvious performance degradation after 90,000 cycles of accelerated aging test, demonstrating excellent stability.
[0049] Polarization and accelerated aging tests were performed on tantalum oxide / carbon-supported high-stability platinum-based fuel cell cathode catalysts in MEA. Figure 5 As shown in Figure 2, the peak power density of the catalyst can reach 2.27 W cm -2 After 50,000 cycles of accelerated aging testing, the performance retention rate was 90%, showing excellent stability.
[0050] Example 2
[0051] The difference between this embodiment and embodiment 1 is that the amount of conductive carbon black (EC-300J) added in step 1) is adjusted to 300 mg, the mass ratio of the metal tantalum source and the carbon source is 1:3, and the remaining steps and processes are all based on embodiment 1 to obtain the tantalum oxide / carbon-loaded high-stability platinum-based fuel cell cathode catalyst of this embodiment.
[0052] The high stability platinum-based fuel cell cathode catalyst of this embodiment was subjected to transmission electron microscopy characterization, particle size statistics, X-ray diffraction characterization, three-electrode stability test, and MEA stability test, and the results were similar to those of Example 1.
[0053] Example 3
[0054] The difference between this embodiment and embodiment 1 is that the amount of conductive carbon black (EC-300J) added in step 1) is adjusted to 350 mg, the mass ratio of the metal tantalum source and the carbon source is 1:3.5, and the remaining steps and processes are all based on embodiment 1 to obtain the tantalum oxide / carbon-loaded high-stability platinum-based fuel cell cathode catalyst of this embodiment.
[0055] The high stability platinum-based fuel cell cathode catalyst of this embodiment was subjected to transmission electron microscopy characterization, particle size statistics, X-ray diffraction characterization, three-electrode stability test, and MEA stability test, and the results were similar to those of Example 1.
[0056] Example 4
[0057] The difference between this embodiment and embodiment 1 is that the amount of conductive carbon black (EC-300J) added in step 1) is adjusted to 400 mg, the mass ratio of the metal tantalum source and the carbon source is 1:4, and the remaining steps and processes are all based on embodiment 1 to obtain the tantalum oxide / carbon-loaded high-stability platinum-based fuel cell cathode catalyst of this embodiment.
[0058] The high stability platinum-based fuel cell cathode catalyst of this embodiment was subjected to transmission electron microscopy characterization, particle size statistics, X-ray diffraction characterization, three-electrode stability test, and MEA stability test, and the results were similar to those of Example 1.
[0059] Comparative Example 1
[0060] The difference between this comparative example and Example 1 is that the method of adjusting the tantalum oxide / carbon carrier to load platinum is a thermal reduction method, specifically:
[0061] 40 mg of tantalum oxide / carbon carrier was dispersed in 40 mL of water, ultrasonicated for 2 h, 1.40 mL of chloroplatinic acid solution (7.4 mg Pt / mL) was added, stirred for 12 h, and dried by rotary evaporation. The dried sample was heat treated in a 5 vol% argon-hydrogen atmosphere at a temperature of 250 °C and a heating rate of 5 °C min -1 , and cooled to room temperature to obtain a tantalum oxide / carbon-supported platinum-based fuel cell cathode catalyst.
[0062] Tantalum oxide / carbon-supported platinum-based fuel cell cathode catalyst was tested in 0.1 mol / L perchloric acid solution. Figure 6 As shown, the half-wave potential is 0.84 V, which is 40 mV lower than that of Example 1.
[0063] Comparative Example 2
[0064] The difference between this comparative example and Example 1 is that the method of adjusting the tantalum oxide / carbon carrier to load platinum is sodium borohydride reduction, specifically:
[0065] 40 mg of tantalum oxide / carbon support was dispersed in 40 mL of water and ultrasonicated for 2 h. 1.40 mL of chloroplatinic acid solution (7.4 mg Pt / mL) was added and stirred for 3 h. 11.5 mg of sodium borohydride was added and stirred for 3 h. The sample was washed with ultrapure water and dried to obtain the tantalum oxide / carbon-supported platinum-based fuel cell cathode catalyst of this comparative example.
[0066] Tantalum oxide / carbon-supported platinum-based fuel cell cathode catalyst was tested in 0.1 mol / L perchloric acid solution. Figure 7 As shown, the half-wave potential is 0.87 V, which is 15 mV lower than that of Example 1.
[0067] Comparative Example 3
[0068] The difference between this comparative example and Example 1 is that the ratio of the tantalum source and the carbon source in step 1) is adjusted. Specifically, the amount of conductive carbon black (EC-300J) is adjusted to 100 and 650 mg, respectively, and the mass ratios of the metal tantalum source and the carbon source are 5:4 and 1:6.5. The remaining steps and processes are all based on Example 1 to obtain the tantalum oxide / carbon-loaded high-stability platinum-based fuel cell cathode catalyst of this comparative example.
[0069] Tantalum oxide / carbon-supported platinum-based fuel cell cathode catalyst was tested in 0.1 mol / L perchloric acid solution. Figure 8 The half-wave potentials shown are 0.85 and 0.855 V, which are 35 and 30 mV lower than those in Example 1, respectively.
[0070] Comparative Example 4
[0071] The difference between this comparative example and Example 1 is that the platinum loading in the catalyst is adjusted, specifically:
[0072] 40 mg of tantalum oxide / carbon carrier was dispersed in 40 mL of water and ultrasonicated for 2 h. 0.35 and 4.05 mL of chloroplatinic acid solution (7.4 mg Pt / mL) were added respectively (so that the platinum loading was 5 wt% and 60 wt%, respectively). The rest of the steps and processes were referred to Example 1 to obtain a tantalum oxide / carbon-supported high-stability platinum-based fuel cell cathode catalyst of this example.
[0073] Tantalum oxide / carbon-supported platinum-based fuel cell cathode catalyst was tested in 0.1 mol / L perchloric acid solution. Fig. 9The half-wave potentials shown are 0.837 and 0.856 V, which are 48 and 29 mV lower than those in Example 1, respectively.
[0074] In summary, the metal oxide composite carrier supported platinum catalyst provided by the present invention utilizes the confinement effect of mesoporous carbon to limit the excessive growth of metal oxides, and forms amorphous TaOx in a low oxidation state at high temperature, so that TaOx is evenly dispersed in the carbon substrate in the form of small particles. Pt is selectively anchored on TaOx, and the size of the formed platinum particles is small, ensuring a high utilization rate of precious metals. The strong corrosion resistance of metal oxides is utilized to effectively solve the problem of catalyst performance loss caused by carbon corrosion. The preparation method is simple, low-cost, and has good reproducibility. The prepared tantalum oxide-supported high-stability platinum-based fuel cell cathode catalyst has higher catalytic activity and better stability than existing commercial catalysts.
[0075] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a tantalum oxide / carbon-supported high-stability platinum-based fuel cell cathode catalyst, characterized in that: include, A metal tantalum source is dissolved in anhydrous ethanol and subjected to ultrasonic treatment to obtain a metal tantalum solution, a carbon source is added thereto, and after ultrasonic treatment, a black solid is obtained by rotary evaporation, wherein the mass ratio of the metal tantalum source to the carbon source is 1:1 to 1:10; The black solid is heat-treated in a reducing atmosphere, and then naturally cooled to room temperature to obtain a tantalum oxide / carbon carrier; Tantalum oxide / carbon carrier is dispersed in ethylene glycol, stirred in chloroplatinic acid aqueous solution added after ultrasound, condensed and refluxed in an oil bath after adjusting the pH of the solution, naturally cooled to room temperature after treatment, filtered and dried to obtain a tantalum oxide / carbon-supported high-stability platinum-based fuel cell cathode catalyst, wherein the platinum loading is 10wt.% to 50wt.%.
2. The method for preparing a tantalum oxide / carbon-supported high-stability platinum-based fuel cell cathode catalyst according to claim 1, characterized in that: The metal tantalum source includes one or more of tantalum chloride and tantalum nitrate.
3. The method for preparing a tantalum oxide / carbon-supported high-stability platinum-based fuel cell cathode catalyst according to claim 1, characterized in that: The carbon source is conductive carbon black.
4. The method for preparing a tantalum oxide / carbon-supported high-stability platinum-based fuel cell cathode catalyst according to claim 2, characterized in that: The ultrasonic time of the metal tantalum source in anhydrous ethanol is 0.5 to 2 hours, and the ultrasonic time after adding the carbon source is 3 to 6 hours.
5. The method for preparing a tantalum oxide / carbon-supported high-stability platinum-based fuel cell cathode catalyst according to claim 1, characterized in that: The reducing atmosphere is a mixture of hydrogen and argon. , Among them, the volume ratio of hydrogen to argon is 17-19:1-3.
6. The method for preparing a tantalum oxide / carbon-supported high-stability platinum-based fuel cell cathode catalyst according to claim 1, characterized in that: The heating rate of the heat treatment is 1-10°C min -1 The heat treatment temperature is 500-1000° C., and the heat treatment time is 0.5-3 h.
7. The method for preparing a tantalum oxide / carbon-supported high-stability platinum-based fuel cell cathode catalyst according to claim 1, characterized in that: The pH of the chloroplatinic acid aqueous solution is adjusted to 9-12.
8. A tantalum oxide / carbon-supported high-stability platinum-based fuel cell cathode catalyst prepared by the preparation method according to any one of claims 1 to 7.
9. A tantalum oxide / carbon-supported high-stability platinum-based fuel cell cathode catalyst, characterized in that: The platinum nanoparticles in the high-stability platinum-based fuel cell cathode catalyst are uniformly loaded on the surface of the tantalum oxide / carbon carrier, and the average particle size of the platinum nanoparticles is 3.0 nm.
10. The tantalum oxide / carbon-supported high-stability platinum-based fuel cell cathode catalyst according to claim 8, characterized in that: The high-stability platinum-based fuel cell cathode catalyst has no obvious performance degradation after undergoing 90,000 cycles of accelerated aging test in a 0.1 mol / L perchloric acid solution; Peak power density in MEA reaches 2.27 W cm -2 , after 50,000 cycles of accelerated aging testing, the performance retention rate is 90%.